Complete Genome of Lactococcus lactis subsp. cremoris UC509.9, Host for a Model Lactococcal P335 Bacteriophage - Ainsworth, Stuart (American Society for Microbiology, 2013)
Here, we report the complete genome of Lactococcus lactis subsp. cremoris UC509.9, an Irish dairy starter. The circular chromosome of L. lactis UC509.9 represents the smallest among those of the sequenced lactococcal strains, while its large complement of eight plasmids appears to be a reflection of its adaptation to the dairy environment.